Small molecule glucagon release inhibitors with activity in human islets - Kalwat, Michael A.; Rodrigues-dos-Santos, Karina; Binns, Derk D.; Wei, Shuguang; Zhou, Anwu; Evans, Matthew R.; Posner, Bruce A.; Roth, Michael G.; Cobb, Melanie H. (Frontiers in Endocrinology, 2023)
Type 1 diabetes (T1D) accounts for an estimated 5% of all diabetes in the United States, afflicting over 1.25 million individuals. Maintaining long-term blood glucose control is the major goal for individuals with T1D. In T1D, insulin-secreting pancreatic islet β-cells are destroyed by the immune system, but glucagon-secreting islet α-cells survive. These remaining α-cells no longer respond properly to fluctuating blood glucose concentrations. Dysregulated α-cell function contributes to hyper- and hypoglycemia which can lead to macrovascular and microvascular complications. To this end, we sought to discover small molecules that suppress α-cell function for their potential as preclinical candidate compounds. Prior high-throughput screening identified a set of glucagon-suppressing compounds using a rodent α-cell line model, but these compounds were not validated in human systems. Here, we dissociated and replated primary human islet cells and exposed them to 24 h treatment with this set of candidate glucagon-suppressing compounds. Glucagon accumulation in the medium was measured and we determined that compounds SW049164 and SW088799 exhibited significant activity. Candidate compounds were also counter-screened in our InsGLuc-MIN6 β-cell insulin secretion reporter assay. SW049164 and SW088799 had minimal impact on insulin release after a 24 h exposure. To further validate these hits, we treated intact human islets with a selection of the top candidates for 24 h. SW049164 and SW088799 significantly inhibited glucagon release into the medium without significantly altering whole islet glucagon or insulin content. In concentration-response curves SW088799 exhibited significant inhibition of glucagon release with an IC50 of 1.26 µM. Given the set of tested candidates were all top hits from the primary screen in rodent α-cells, this suggests some conservation of mechanism of action between human and rodents, at least for SW088799. Future structure-activity relationship studies of SW088799 may aid in elucidating its protein target(s) or enable its use as a tool compound to suppress α-cell activity in vitro.